Measurement of cow manure compost toxicity and maturity based on weed seed germination. (1st February 2020) - Liu, Tao; Wang, Meijing; Awasthi, Mukesh Kumar; Chen, Hongyu; Awasthi, Sanjeev Kumar; Duan, Yumin; Zhang, Zengqiang
Abstract: There are many weed seeds that maintain their viability in cow manure (COM), which not only poses a serious threat to agriculture if the manure is applied to the fields directly, but also affects the food security. Composting is an essential process that transforms COM into fertilizer and reduces the plant diseases or weed seeds. In the scientific literature, there are many investigations on the effect of temperature, electrical conductivity, and pH on the viability of the weed seeds, but very few reports dealt with the combined influence of the above factors with volatile fatty acids (acetic acid) and toxic metals on the deactivation of weed seeds. The aim of this study was to investigate the compost toxicity and maturity by a seed germination test. The viability of 8 types of weed seeds was investigated in separate glass fermentation tanks during the COM composting for 45 d. The seed viability was determined by the triphenyl tetrazole chloride method. The results revealed that all the weed seeds were killed in the process of composting, with 7 weed seeds inactivated within 110 h at temperatures below 60 °C, while the 8th seed, field bindweed was an exception. This could be attributed to the large volume of the seed; however, the follow-up process could destroy the field bindweed as well. The significant correlations among various physicochemical parameters, volatile fatty acids, toxic metals and viability weed seeds are found by redundancy analyses. This study could be considered a benchmark that suggests that the use of composted COM involves a small risk of enhancing the abundance of weed seeds. The aerobic composting appears to be an efficient way to treat the COM in a way that suppresses the parasitic weeds so that the COM could be applied without risking the pets. Graphical abstract: Image 106 Highlights: The viability of weed seeds during the composting of COM was investigated. Seven weed seeds in the COM were killed within 110 h (at a temperature below 60 °C). The temperature played a critical role in eliminating the germination of weed seeds. The application of compost has not increased the risk of weed seed abundance.